TINJAUAN YURIDIS TERHADAP PEMBATALAN AKTA NOTARIS - Hermawan, Moh Syahrul; Qahar, Abdul; Risma, Andi (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2022)
ABSTRAC This study aims to find out and analyze the legal consequences for a notary against a deed canceled by the court and to find out and analyze the factors causing the cancellation of a deed by the court. This research uses normative legal researchmethods using normative case studies in the form of legal behavior. The subject ofthe study is the law which is conceptualized as a norm or rule that applies in societyand becomes a reference for everyones behavior. So that normative legal researchfocuses on an inventory of positive law, legal principles and doctrines, legal findings in concrete cases, legal systematics, legal comparisons and legal history. laws andregulations The results of this study indicate that from the results of research with the research method and approach used by the author, that the factors causing the cancellation of a deed by the court were because the deed was not read out beforethe parties, there was an element of coercion to sign the deed and the formalrequirements were not fulfilled in making the deed. deed. The author identifies thatthe responsibility of a notary if the deed is canceled due to negligence is to pay compensation to the parties, whether real (material) or intangible (immaterial)compensation. The implication of the research results is that the notary in makingthe deed acts professionally, honestly, and carefully. In addition, the parties whowant to make a deed by a notary to act honestly or provide actual information inmaking a deed by a notary. ABSTRAK Penelitian ini bertujuan Untuk mengetahui dan menganalisis akibat hukum bagi Notaris terhadap akta yang dibatalkan oleh pengadilan Dan Untuk mengetahui danmenganalisis faktor-faktor penyebab dibatalkannya suatu akta oleh pengadilanPenelitian ini menggunakan metode penelitian hukum Normatif menggunakan studi kasus normatif berupa perilaku hukum. Pokok kajiannya adalah hukum yang dikonsepkan sebagai norma atau kaidah yang berlaku dalam masyarakat danmenjadi acuan perilaku setiap orang. Hasil penelitian ini menunjuakan bahwa Darihasil penelitian dengan metode dan pendekatan penelitian yang digunakan penulis, bahwasanya faktor-faktor penyebab dibatalkannya suatu akta oleh pengadilankarena tidak dibacakannya akta dihadapan para pihak, adanya unsur pemaksaanuntuk menandatangani akta dan adanya syarat formil yang tidak terpenuhi dalampembuatan akta. Mengidentifikasi bahwasanya tanggungjawab seorang notaris apabila akta dibatalkan karena kelalaiannya adalah membayar ganti rugi kepada para pihak baik itu ganti rugi yang nyata (materil) maupun tidak nyata(immateril).Implikasi dari hasil penelitian adalah agar kiranya notaris dalam membuat akta bertindak profesioanlitas, jujur, dan cermat. Selain itu para pihak yang ingin dibuatkan akta oleh notaris untuk bertindak jujur atau memberikan keterangan yang sebenarnya dalam pembuatan akta oleh notaris.